Efficient subsidization of human capital accumulation with overlapping generations and endogenous growth - Wolfram F. Richter; Christoph Braun (Institute for the Study of Labor (IZA), 2009)
This paper studies second-best policies in an OLG model in which endogenous growth results from human capital accumulation. When young, individuals decide on education, saving, and nonqualified labour. When old, individuals supply qualified labour. Growth equilibria are inefficient in laissez-faire because of distortionary taxation. The inefficiency is exacerbated if selfish individuals externalize the positive effect of education on descendents' productivity. It is shown to be second best not to distort education if the human capital investment function is isoelastic. If the function is not isoelastic, a case is made for subsidizing education even relative to the first best.
Keywords: H21; I28; J24; 330; OLG model; endogenous growth; endogenous labour; education and saving; intergenerational externalities; optimal taxation; Bildungsinvestition; Bildungsverhalten; Sparen; Einkommensteuer; Optimale Besteuerung; Overlapping Generations; Neue Wachstumstheorie; Theorie